Consolidación de estados financieros de la empresa “Air Brush” spa y peluquería, ubicada en la provincia de Cotopaxi, cantón Latacunga en el periodo del 1 de julio al 30 de septiembre del 2015 - Chiliquinga Toapanta, Paulina Elizabeth (2016)
The consolidation of financial statements is an important issue because it allows knowing in a reasonable way the economic situation of enterprises as whether it will be just one. "AIR BRUSH" has a parent and a subsidiary enterprise, that is the reason which it wants to consolidate the financial statements by applying the current regulations. It took into consideration the non-experimental research model as a methodology and analysis techniques such as survey and interview; they have to know relevant data of accounting and business movements that manage the entity….